ISLAMIC COMMUNICATION EPISTEMOLOGY: AN INTEGRATIVE ANALYSIS OF REVELATION, REASON, AND EXPERIENCE AS SOURCES OF KNOWLEDGE - Annisa Ariftha; Mailin Mailin (Journal Analytica Islamica, 2026)
This article discusses the epistemology of Islamic Communication as an important foundation for the development of Islamic Communication Studies as an independent scientific discipline. This study begins with fundamental questions regarding the sources, processes, and validity of knowledge from an Islamic perspective. In the tradition of the philosophy of science, epistemology serves to explain how knowledge is acquired, tested, and constructed into a credible scientific system. Unlike Western epistemology, which tends to emphasize reason and empirical experience, Islamic epistemology combines revelation, reason, sensory experience, intuition, and social reality as complementary sources of knowledge. This article emphasizes that the Qur'an and Sunnah are the primary sources in forming the normative and ethical foundations of Islamic Communication. Furthermore, the universe, the human self, and human history are also understood as sources of knowledge that enrich the epistemological construction of communication. The integration of these various sources demonstrates that Islamic Communication is not only oriented towards conveying messages but also contains spiritual, moral, social, and scientific dimensions. Thus, Islamic Communication Studies can be developed through an interdisciplinary approach that connects revealed texts with empirical reality. This study concludes that Islamic Communication has objects of study, methods, systematics, utility values, and a basis for truth that enable it to stand as an independent discipline. Strengthening its epistemology is a strategic step in developing communication theory grounded in Islamic values and relevant to the needs of contemporary society.